2011
DOI: 10.1117/12.902308
|View full text |Cite
|
Sign up to set email alerts
|

The design of the Langmuir probe onboard a seismo-electromagnetic satellite

Abstract: The double Langmuir probe, as a payload of a seism-electromagnetic satellite, has been designed for in situ measurements of the parameters of the ionosphere plasma on the 500km altitude orbit to research the electromagnetic coupling between the solid-earth activities and the ionosphere disturbances. The Langmuir probe is comprised of two spherical sensors: the diameter of the smaller one is 1cm and the other one is 5cm. The two sensors are mounted on two parallel booms on the satellite, which are half meter fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Therefore, the accuracy of Ne depends on the accuracy of, I e0 (Wang et al, 2019a). The relative accuracy is less than 10% when Ne is in the measurement range of 5×10 2 to 1×10 7 / cm 3 according to the LAP designer (Guan et al, 2011). Therefore, Ne must be in the measurement range to keep its relative accuracy.…”
Section: The Satellite and The Ne Measurementsmentioning
confidence: 99%
“…Therefore, the accuracy of Ne depends on the accuracy of, I e0 (Wang et al, 2019a). The relative accuracy is less than 10% when Ne is in the measurement range of 5×10 2 to 1×10 7 / cm 3 according to the LAP designer (Guan et al, 2011). Therefore, Ne must be in the measurement range to keep its relative accuracy.…”
Section: The Satellite and The Ne Measurementsmentioning
confidence: 99%
“…Sensor 1 is a larger one with a diameter of 5 cm, and the diameter of sensor 2 is 1 cm, designed as a backup. There is a long stub 50 cm in length for each sensor to reduce the interference from the satellite surface [18]. The data we used in this study were observed by sensor 1.…”
Section: Datamentioning
confidence: 99%